Methanol fuel automobile exhaust purification catalyst
By using the combination of pre-stage catalyst and post-stage catalyst in methanol fuel vehicle exhaust purification catalyst, and using components such as rare earths, cobalt ferrous materials and metal oxides, the problem of poor exhaust purification performance of existing catalysts is solved, and the problem of poor exhaust purification performance is achieved. Efficient removal of various pollutants in the exhaust gas of methanol fuel vehicles and has excellent heat resistance.
Patent Information
- Application Number
- CN202411447968.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The exhaust purification performance of existing methanol fuel automobile exhaust purification catalysts is poor and fails to effectively remove pollutants such as methanol and formaldehyde.
A catalyst system consisting of pre-stage catalysts and post-stage catalysts. The pre-stage catalyst consists of high cerium rare earths, cobalt black materials, metal oxides, etc. The post-stage catalyst consists of high zirconium rare earths, metal oxides, etc., and passes through rare earths and cobalt black. The combination of materials and metal oxides and other components significantly improves the purification performance of the catalyst.
It significantly improves the catalyst's exhaust purification performance on methanol fuel vehicles, can effectively remove pollutants such as CO, THC, NMHC, CH4, NOx, and has excellent heat shock resistance and can withstand high temperatures of 1000℃.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile exhaust purification, and in particular to a catalyst for purifying automobile exhaust using methanol fuel. Background Art
[0002] With the development of the automobile industry, methanol is regarded as the most promising and optimal alternative fuel for automobiles because its physical and chemical properties are similar to those of gasoline and the production of methanol has very abundant raw materials (coal, natural gas, biological resources, etc.). At present, the development of methanol-fueled vehicles also plays an important role in the development of my country's automobile industry. However, the main pollutants emitted by methanol-fueled vehicles are a large amount of unburned methanol and incomplete combustion products such as formaldehyde, which pose a serious threat to the environment and human body and must be purified.
[0003] Catalysts installed in automobile exhaust systems can purify exhaust gas. Currently, these catalysts are usually three-way catalysts. Three-way catalysts consist of two parts: a carrier and an active catalytic substance coated on the carrier; the active catalytic substance is usually a precious metal, such as one or more of platinum, palladium and rhodium, and an oxidizing material is added. From the existing methanol fuel automobile exhaust purification catalysts, they have not yet met the real practical requirements in terms of catalytic activity and deep redox performance.
[0004] Therefore, the development of methanol fuel vehicle exhaust purification catalysts with excellent exhaust purification performance will be of great significance to my country's automobile industry, energy structure and other aspects. Summary of the invention
[0005] The invention provides a methanol fuel automobile exhaust gas purification catalyst, which solves the problem of poor exhaust gas purification performance of methanol fuel automobile exhaust gas purification catalyst in the related art.
[0006] The technical solution of the present invention is as follows:
[0007] The present invention provides a methanol fuel automobile exhaust purification catalyst, comprising a front-stage catalyst and a rear-stage catalyst;
[0008] The raw materials of the pre-stage catalyst include pre-stage rare earth main material, pre-stage active material and pre-stage auxiliary material;
[0009] The raw materials of the latter catalyst include a latter rare earth main material, a latter active material and a latter auxiliary material;
[0010] The main materials of the previous rare earth include high cerium rare earth, medium cerium and medium zirconium rare earth, previous metal oxides, previous noble metals and cobalt black material;
[0011] The secondary rare earth main material includes high-zirconium rare earth, medium-cerium and medium-zirconium rare earth, secondary metal oxides and secondary noble metals;
[0012] The cerium content of the high cerium rare earth is 50wt%~60wt%; the cerium content of the medium cerium-zirconium rare earth is 30wt%~40wt%, and the zirconium content is 40wt%~50wt%; the zirconium content of the high zirconium rare earth is 60wt%~70wt%.
[0013] As a further technical solution, the cobalt content of the cobalt black material is 40wt%~50wt%.
[0014] As a further technical solution, the front-stage metal oxide and the back-stage metal oxide each independently include one or more of nano titanium dioxide, nano aluminum oxide, and lanthanum-modified aluminum oxide.
[0015] As a further technical solution, the nano titanium dioxide is tungsten-containing nano titanium dioxide, and the tungsten content is 2wt%~10wt%.
[0016] As a further technical solution, the front-stage active material and the rear-stage active material each independently include an organic acid and a metal salt.
[0017] As a further technical solution, the organic acid is one or more of citric acid, malic acid, oxalic acid, and tartaric acid;
[0018] The metal salt is one or more of cobalt salt, manganese salt, barium salt and nickel salt.
[0019] As a further technical solution, the front-stage auxiliary material and the rear-stage auxiliary material each independently include a thickener, a pH regulator and water.
[0020] As a further technical solution, the thickener is one or both of aluminum sol and cellulose thickener; and the pH regulator is an acidic pH regulator.
[0021] The present invention also provides a methanol fuel automobile exhaust purification catalyst, which is calculated by weight:
[0022] The raw materials of the preceding catalyst include 1500-1520 parts of preceding rare earth main material, 80-111 parts of preceding active material and 3846-4210 parts of preceding auxiliary material;
[0023] The raw materials of the rear-stage catalyst include 1500 parts of rear-stage rare earth main material, 90 parts of rear-stage active material and 4210-4212 parts of rear-stage auxiliary material;
[0024] The main material of the previous rare earth includes 580-700 parts of high cerium rare earth, 300-400 parts of medium cerium and medium zirconium rare earth, 500-510 parts of the previous metal oxide, and 5-30 parts of cobalt black material;
[0025] The secondary rare earth main material comprises 700-800 parts of high-zirconium rare earth, 200-300 parts of medium-cerium and medium-zirconium rare earth, and 500 parts of secondary metal oxide.
[0026] As a further technical solution, the front-stage precious metal includes Pt, Pd and Rh; the rear-stage precious metal includes Pd and Rh.
[0027] As a further technical solution, the aluminum sol includes aluminum sol P4 (07), aluminum sol JHALH-15 and aluminum sol SRJ-01; the cellulose thickener is one or more of hydroxypropyl methylcellulose, hydroxyethyl cellulose, methyl cellulose, hydroxyethyl methyl cellulose and hydroxypropyl cellulose.
[0028] As a further technical solution, the mass ratio of the aluminum sol P4 (07), aluminum sol JHALH-15 and aluminum sol SRJ-01 is 5~10:5:7.
[0029] As a further technical solution, the mass ratio of the nano titanium dioxide, nano aluminum oxide, and lanthanum modified aluminum oxide is 5-7:9-10:10.
[0030] As a further technical solution, the mass ratio of the organic acid to the metal salt is 1-3:3.
[0031] As a further technical solution, when the thickener is aluminum sol and a cellulose thickener, the mass ratio of the aluminum sol to the cellulose thickener is 170:2~4.
[0032] As a further technical solution, the metal salts in the preceding active material are cobalt salts, manganese salts and barium salts.
[0033] As a further technical solution, the metal salts in the later-stage active material are barium salts and nickel salts.
[0034] As a further technical solution, the preparation process of the front-stage catalyst comprises the following steps:
[0035] The preceding stage active material solution, the preceding stage auxiliary material solution and the preceding stage rare earth main material are mixed to obtain a preceding stage catalyst.
[0036] As a further technical solution, the preparation process of the latter catalyst comprises the following steps:
[0037] The post-stage active material solution, the post-stage auxiliary material solution and the post-stage rare earth main material are mixed to obtain a post-stage catalyst.
[0038] As a further technical solution, the method for using the preceding catalyst comprises the following steps: coating the preceding catalyst on the surface of a carrier, and after drying and calcining, the preceding catalyst can be used in exhaust gas purification of methanol fuel vehicles.
[0039] As a further technical solution, the method for using the latter catalyst comprises the following steps: coating the latter catalyst on the surface of a carrier, and after drying and calcining, the catalyst can be used in the exhaust gas purification of methanol fuel vehicles.
[0040] As a further technical solution, the drying temperature is 50-60°C;
[0041] During the calcination, the temperature is first raised to 100° C. at a heating rate of 2.5° C. / min and kept at that temperature for 60 min;
[0042] Then, the temperature was raised from 100°C to 150°C at a heating rate of 1.25°C / min and kept at this temperature for 60 min;
[0043] Then, the temperature was raised from 150°C to 250°C at a heating rate of 1.67°C / min and kept at this temperature for 30 min;
[0044] Then, the temperature was increased from 250°C to 550°C at a heating rate of 1.67°C / min and kept at this temperature for 150-180 minutes.
[0045] In the present invention, a step-by-step heating method is adopted during calcination, wherein the temperature is firstly raised to 100°C and kept for 60 minutes, which can effectively discharge the adsorbed water on the surface of the coating material; then the temperature is raised from 100°C to 150°C and kept for 60 minutes, which can effectively remove the crystal water in the internal structure of the coating material; the temperature is raised from 150°C to 250°C and kept for 30 minutes, which can fully discharge the organic components in the coating material; the temperature is raised from 250°C to 550°C and kept for 150-180 minutes, which can fully ensure the catalytic activity and stability of the catalyst.
[0046] The working principle and beneficial effects of the present invention are:
[0047] In the present invention, the methanol fuel automobile exhaust purification catalyst includes a front-stage catalyst and a rear-stage catalyst. The front-stage catalyst mainly purifies CO, THC, NMHC, CH 4 The rear catalyst mainly purifies NOx and other pollutants. By adding rare earth, cobalt black material, metal oxide, metal salt and other components to the catalyst, the cobalt black material is conducive to purifying CO, and the metal oxide and other components are conducive to purifying formaldehyde and methanol. The organic combination of the front stage and the rear stage and the mutual coordination of each component ultimately significantly improve the catalyst's performance in purifying methanol fuel automobile exhaust, and the methanol fuel automobile exhaust purification catalyst of the present invention has excellent heat shock resistance and can withstand a high temperature of 1000°C. DETAILED DESCRIPTION
[0048] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] In the following examples and comparative examples, the information of the raw materials used is shown in Table 1 below.
[0050] Table 1 Raw material information
[0051]
[0052] The preparation method of cobalt black material comprises the following steps:
[0053] Lanthanum nitrate, cerium nitrate, cobalt nitrate, and ferric nitrate are stirred and mixed with deionized water at 80°C until dissolved, aluminum oxide is added and stirred and mixed until a viscous mass is formed, and the viscous mass is dried and roasted to obtain a cobalt black material; wherein the roasting temperature is 750-760°C, and the time is 2.5h; the mass ratio of aluminum oxide, lanthanum nitrate, cerium nitrate, cobalt nitrate and ferric nitrate is 26:4:12:46:12; and the cobalt content of the cobalt black material is 46wt%.
[0054] Example 1
[0055] Methanol fuel automobile exhaust purification catalyst, including front-stage catalyst and rear-stage catalyst;
[0056] The raw materials of the front-stage catalyst include, by weight:
[0057] Pre-stage rare earth main materials: 700 parts of high cerium rare earth, 300 parts of medium cerium and medium zirconium rare earth, 10 parts of cobalt black material, 120 parts of nano titanium dioxide, 180 parts of nano alumina, 200 parts of lanthanum modified alumina,
[0058] Pre-active material: 20 parts of barium acetate, 60 parts of citric acid,
[0059] Pre-stage auxiliary materials: 100 parts of aluminum sol JHALH-15, 200 parts of aluminum sol P4 (07), 140 parts of aluminum sol SRJ-01, 16 parts of nitric acid, 3460 parts of deionized water,
[0060] Precursor noble metals: Pt 1.6 parts, Pd 6 parts, Rh 2.4 parts;
[0061] The raw materials of the rear stage catalyst include, by weight:
[0062] The main materials of the rear rare earth are: 800 parts of high zirconium rare earth, 200 parts of medium cerium and medium zirconium rare earth, 100 parts of nano titanium dioxide, 200 parts of nano alumina, and 200 parts of lanthanum modified alumina.
[0063] Post-stage active materials: 20 parts of barium acetate, 10 parts of nickel nitrate, 60 parts of citric acid,
[0064] Post-stage auxiliary materials: 100 parts of aluminum sol JHALH-15, 100 parts of aluminum sol P4 (07), 140 parts of aluminum sol SRJ-01, 6 parts of hydroxypropyl methylcellulose, 14 parts of nitric acid, and 3850 parts of deionized water;
[0065] Secondary precious metals: Pd 2.4 parts, Rh 3.6 parts;
[0066] The preparation process of the front-stage catalyst comprises the following steps:
[0067] S1. The previous active material is dissolved in 500 parts of deionized water to obtain a previous active material solution;
[0068] S2, dissolving aluminum sol JHALH-15, aluminum sol P4 (07), and aluminum sol SRJ-01 in 2000 parts of deionized water to obtain an aluminum sol solution;
[0069] S3, after mixing the previous active material solution and the aluminum sol solution for 20 minutes, adding the previous rare earth main material and stirring, adjusting the pH to 4.0-4.1, grinding at a speed of 2000r / min to obtain the previous slurry A; wherein nitric acid and deionized water are used when adjusting the pH;
[0070] S4, mixing the previous noble metal and 120 parts of citric acid aqueous solution (the mass ratio of citric acid to water is 1:10) to obtain a previous noble metal solution;
[0071] S5. Add the previous stage noble metal solution dropwise into the previous stage slurry A, stir and mix, and obtain the previous stage catalyst.
[0072] The preparation process of the rear stage catalyst comprises the following steps:
[0073] T1, the post-stage active material is dissolved in 500 parts of deionized water to obtain a post-stage active material solution;
[0074] T2, dissolving aluminum sol JHALH-15, aluminum sol P4 (07), and aluminum sol SRJ-01 in 2000 parts of deionized water to obtain an aluminum sol solution;
[0075] T3, after mixing the post-stage active material solution and the aluminum sol solution for 20 minutes, adding the post-stage rare earth main material and stirring, adjusting the pH to 4.0-4.1, adding hydroxypropyl methylcellulose and continuing to stir for 30 minutes, adjusting the pH to 4.0-4.1, grinding at a speed of 2000r / min to obtain a post-stage slurry A; wherein nitric acid and deionized water are used when adjusting the pH;
[0076] T4, mixing the subsequent noble metal and 63 parts of citric acid aqueous solution (the mass ratio of citric acid to water is 1:10) to obtain a subsequent noble metal solution;
[0077] T5. Add the subsequent noble metal solution dropwise into the subsequent slurry A, stir and mix, and obtain a subsequent catalyst.
[0078] Example 2
[0079] The difference between this embodiment and embodiment 1 is that the front-stage catalyst includes the following raw materials in parts by weight:
[0080] Pre-stage rare earth main materials: 580 parts of high cerium rare earth, 400 parts of medium cerium and medium zirconium rare earth, 30 parts of cobalt black material, 120 parts of nano titanium dioxide, 180 parts of nano alumina, 200 parts of lanthanum modified alumina,
[0081] Pre-active material: 20 parts of barium acetate, 60 parts of citric acid,
[0082] Pre-stage auxiliary materials: 100 parts of aluminum sol JHALH-15, 100 parts of aluminum sol P4 (07), 140 parts of aluminum sol SRJ-01, 6 parts of hydroxypropyl methylcellulose, 15 parts of nitric acid, 3848 parts of deionized water,
[0083] Precursor noble metals: Pt 1.6 parts, Pd 6 parts, Rh 2.4 parts;
[0084] The preparation process of the front-stage catalyst comprises the following steps:
[0085] S1. The previous active material is dissolved in 500 parts of deionized water to obtain a previous active material solution;
[0086] S2, dissolving aluminum sol JHALH-15, aluminum sol P4 (07), and aluminum sol SRJ-01 in 2000 parts of deionized water to obtain an aluminum sol solution;
[0087] S3, after mixing the previous active material solution and the aluminum sol solution for 20 minutes, adding the previous rare earth main material and stirring, adjusting the pH to 4.0-4.1, adding hydroxypropyl methylcellulose and continuing to stir for 30 minutes, adjusting the pH to 4.0-4.1, grinding at a speed of 2000r / min to obtain the previous slurry A; wherein nitric acid and deionized water are used when adjusting the pH;
[0088] S4, mixing the previous noble metal and 120 parts of citric acid aqueous solution (the mass ratio of citric acid to water is 1:10) to obtain a previous noble metal solution;
[0089] S5. Add the previous stage noble metal solution dropwise into the previous stage slurry A, stir and mix, and obtain the previous stage catalyst.
[0090] Example 3
[0091] The difference between this embodiment and embodiment 1 is that the front-stage catalyst includes the following raw materials in parts by weight:
[0092] Pre-stage rare earth main materials: 700 parts of high cerium rare earth, 300 parts of medium cerium and medium zirconium rare earth, 10 parts of cobalt black material, 120 parts of nano titanium dioxide, 180 parts of nano alumina, 200 parts of lanthanum modified alumina,
[0093] Pre-active materials: 16 parts of manganese acetate, 30 parts of barium acetate, 60 parts of citric acid,
[0094] Pre-stage auxiliary materials: 100 parts of aluminum sol JHALH-15, 100 parts of aluminum sol P4 (07), 140 parts of aluminum sol SRJ-01, 4 parts of hydroxypropyl methylcellulose, 15 parts of nitric acid, 3851 parts of deionized water,
[0095] Precursor noble metals: Pt 1.6 parts, Pd 6 parts, Rh 2.4 parts;
[0096] The preparation process of the front-stage catalyst comprises the following steps:
[0097] S1. The previous active material is dissolved in 500 parts of deionized water to obtain a previous active material solution;
[0098] S2, dissolving aluminum sol JHALH-15, aluminum sol P4 (07), and aluminum sol SRJ-01 in 2000 parts of deionized water to obtain an aluminum sol solution;
[0099] S3, after mixing the previous active material solution and the aluminum sol solution for 20 minutes, adding the previous rare earth main material and stirring, adjusting the pH to 4.0-4.1, adding hydroxypropyl methylcellulose and continuing to stir for 30 minutes, adjusting the pH to 4.0-4.1, grinding at a speed of 2000r / min to obtain the previous slurry A; wherein nitric acid and deionized water are used when adjusting the pH;
[0100] S4, mixing the previous noble metal and 120 parts of citric acid aqueous solution (the mass ratio of citric acid to water is 1:10) to obtain a previous noble metal solution;
[0101] S5. Add the previous stage noble metal solution dropwise into the previous stage slurry A, stir and mix, and obtain the previous stage catalyst.
[0102] Example 4
[0103] The difference between this embodiment and embodiment 1 is that the front-stage catalyst includes the following raw materials in parts by weight:
[0104] Pre-stage rare earth main materials: 700 parts of high cerium rare earth, 300 parts of medium cerium and medium zirconium rare earth, 5 parts of cobalt black material, 120 parts of nano titanium dioxide, 180 parts of nano alumina, 200 parts of lanthanum modified alumina,
[0105] Pre-stage active material: 10 parts of cobalt nitrate, 20 parts of barium acetate, 60 parts of citric acid,
[0106] Pre-stage auxiliary materials: 100 parts of aluminum sol JHALH-15, 100 parts of aluminum sol P4 (07), 140 parts of aluminum sol SRJ-01, 6 parts of hydroxypropyl methylcellulose, 16 parts of nitric acid, 3832 parts of deionized water,
[0107] Precursor noble metals: Pt 1.6 parts, Pd 6 parts, Rh 2.4 parts;
[0108] The preparation process of the front-stage catalyst comprises the following steps:
[0109] S1. The previous active material is dissolved in 500 parts of deionized water to obtain a previous active material solution;
[0110] S2, dissolving aluminum sol JHALH-15, aluminum sol P4 (07), and aluminum sol SRJ-01 in 2000 parts of deionized water to obtain an aluminum sol solution;
[0111] S3, after mixing the previous active material solution and the aluminum sol solution for 20 minutes, adding the previous rare earth main material and stirring, adjusting the pH to 4.0-4.1, adding hydroxypropyl methylcellulose and continuing to stir for 30 minutes, adjusting the pH to 4.0-4.1, grinding at a speed of 2000r / min to obtain the previous slurry A; wherein nitric acid and deionized water are used when adjusting the pH;
[0112] S4, mixing the previous noble metal and 120 parts of citric acid aqueous solution (the mass ratio of citric acid to water is 1:10) to obtain a previous noble metal solution;
[0113] S5. Add the previous stage noble metal solution dropwise into the previous stage slurry A, stir and mix, and obtain the previous stage catalyst.
[0114] Example 5
[0115] The difference between this embodiment and embodiment 1 is that the front-stage catalyst includes the following raw materials in parts by weight:
[0116] Pre-stage rare earth main materials: 700 parts of high cerium rare earth, 300 parts of medium cerium and medium zirconium rare earth, 10 parts of cobalt black material, 130 parts of nano titanium dioxide, 180 parts of nano alumina, 200 parts of lanthanum modified alumina,
[0117] Pre-stage active materials: 5 parts of cobalt nitrate, 16 parts of manganese acetate, 30 parts of barium acetate, 60 parts of citric acid,
[0118] Pre-stage auxiliary materials: 100 parts of aluminum sol JHALH-15, 100 parts of aluminum sol P4 (07), 140 parts of aluminum sol SRJ-01, 6.5 parts of hydroxypropyl methylcellulose, 16 parts of nitric acid, 3840 parts of deionized water,
[0119] Precursor noble metals: Pt 1.6 parts, Pd 6 parts, Rh 2.4 parts;
[0120] The preparation process of the front-stage catalyst comprises the following steps:
[0121] S1. The previous active material is dissolved in 500 parts of deionized water to obtain a previous active material solution;
[0122] S2, dissolving aluminum sol JHALH-15, aluminum sol P4 (07), and aluminum sol SRJ-01 in 2000 parts of deionized water to obtain an aluminum sol solution;
[0123] S3, after mixing the previous active material solution and the aluminum sol solution for 20 minutes, adding the previous rare earth main material and stirring, adjusting the pH to 4.0-4.1, adding hydroxypropyl methylcellulose and continuing to stir for 30 minutes, adjusting the pH to 4.0-4.1, grinding at a speed of 2000r / min to obtain the previous slurry A; wherein nitric acid and deionized water are used when adjusting the pH;
[0124] S4, mixing the previous noble metal and 120 parts of citric acid aqueous solution (the mass ratio of citric acid to water is 1:10) to obtain a previous noble metal solution;
[0125] S5. Add the previous stage noble metal solution dropwise into the previous stage slurry A, stir and mix, and obtain the previous stage catalyst.
[0126] Example 6
[0127] The difference between this embodiment and embodiment 4 is that the raw materials of the rear stage catalyst include, by weight:
[0128] The main ingredients of the rear rare earth are: 700 parts of high zirconium rare earth, 300 parts of medium cerium and medium zirconium rare earth, 100 parts of nano titanium dioxide, 200 parts of nano alumina, and 200 parts of lanthanum modified alumina.
[0129] Post-stage active materials: 20 parts of barium acetate, 10 parts of nickel nitrate, 60 parts of citric acid,
[0130] Post-stage auxiliary materials: 100 parts of aluminum sol JHALH-15, 100 parts of aluminum sol P4 (07), 140 parts of aluminum sol SRJ-01, 6 parts of hydroxypropyl methylcellulose, 16 parts of nitric acid, and 3860 parts of deionized water;
[0131] Post-stage precious metals: Pd 2.4 parts, Rh 3.6 parts.
[0132] Comparative Example 1
[0133] The difference between this comparative example and Example 1 is that the raw materials of the pre-stage catalyst include, by weight:
[0134] Pre-stage rare earth main materials: 700 parts of high cerium rare earth, 300 parts of medium cerium and medium zirconium rare earth, 120 parts of nano titanium dioxide, 180 parts of nano alumina, 200 parts of lanthanum modified alumina,
[0135] Pre-active material: 20 parts of barium acetate, 60 parts of citric acid,
[0136] Pre-stage auxiliary materials: 100 parts of aluminum sol JHALH-15, 200 parts of aluminum sol P4 (07), 140 parts of aluminum sol SRJ-01, 16 parts of nitric acid, 3390 parts of deionized water,
[0137] Precursor noble metals: Pt 1.6 parts, Pd 6 parts, Rh 2.4 parts;
[0138] The preparation process of the front-stage catalyst comprises the following steps:
[0139] S1. The previous active material is dissolved in 500 parts of deionized water to obtain a previous active material solution;
[0140] S2, dissolving aluminum sol JHALH-15, aluminum sol P4 (07), and aluminum sol SRJ-01 in 2000 parts of deionized water to obtain an aluminum sol solution;
[0141] S3, after mixing the previous active material solution and the aluminum sol solution for 20 minutes, adding the previous rare earth main material and stirring, adjusting the pH to 4.0-4.1, grinding at a speed of 2000r / min to obtain the previous slurry A; wherein nitric acid and deionized water are used when adjusting the pH;
[0142] S4, mixing the previous noble metal and 120 parts of citric acid aqueous solution (the mass ratio of citric acid to water is 1:10) to obtain a previous noble metal solution;
[0143] S5. Add the previous stage noble metal solution dropwise into the previous stage slurry A, stir and mix, and obtain the previous stage catalyst.
[0144] WHTC Trial
[0145] The front-stage catalysts prepared in Examples 1 to 6 and Comparative Example 1 were coated on the front-stage carrier and the rear-stage catalysts were coated on the rear-stage carrier, respectively, and dried, calcined and packaged at 50° C., and WHTC tests were carried out on a methanol engine 7L-National VI test bench.
[0146] During calcination, the temperature was first raised to 100°C at a heating rate of 2.5°C / min and kept at that temperature for 60 min;
[0147] Then, the temperature was raised from 100°C to 150°C at a heating rate of 1.25°C / min and kept at this temperature for 60 min;
[0148] Then, the temperature was raised from 150°C to 250°C at a heating rate of 1.67°C / min and kept at this temperature for 30 min;
[0149] Then, the temperature was increased from 250°C to 550°C at a heating rate of 1.67°C / min and kept at this temperature for 150 minutes.
[0150] Engine model: A07N;
[0151] The size of the front stage is 10.5×4 inches, and the specification of the front stage carrier is Φ266.7×101.6;
[0152] The size of the rear stage is 10.5×4 inches, and the specification of the rear stage carrier is Φ266.7×101.6;
[0153] Technical route: equivalent combustion + EGR + TWC front stage + TWC rear stage.
[0154] The test results are summarized in Tables 2~3.
[0155] Table 2 WHTC test results
[0156]
[0157] Table 3 WHTC test results
[0158]
[0159] It can be found from Tables 2 to 3 above that, compared with Comparative Example 1, the catalysts prepared in Examples 1 to 6 have lower CO emissions and a CO conversion rate of more than 95% as shown in the WHTC bench test, especially in Example 5, where the CO conversion rate reaches 98.49%, indicating that the addition of cobalt black material to the front-stage catalyst has a stronger ability to purify CO.
[0160] The front and rear stages of the catalysts prepared in Examples 1 to 6 cooperate with each other, so that the emission values of methanol, formaldehyde, methane, NOx, THC, and NMHC are far below the standard limits. The conversion rate of methanol can reach 99.99%, the formaldehyde conversion rate can reach 99.93%, the NOx conversion rate can reach 94.65%, the THC conversion rate can reach 99.88%, and the NMHC conversion rate can reach 99.99%. It can be seen that the catalyst prepared by the present invention has excellent performance in purifying exhaust gas from methanol fueled vehicles. The emission value of formaldehyde for the catalysts prepared in Examples 1 to 3 and 5 can be as low as 0.001 g / kwh, and the catalyst prepared in Example 3 can make the emission value of methanol as low as 0.004 g / kwh.
[0161] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A methanol fuel automobile exhaust purification catalyst, characterized in that: The methanol fuel automobile exhaust purification catalyst comprises a front-stage catalyst and a rear-stage catalyst; The raw materials of the pre-stage catalyst include pre-stage rare earth main material, pre-stage active material and pre-stage auxiliary material; The raw materials of the latter catalyst include a latter rare earth main material, a latter active material and a latter auxiliary material; The main materials of the previous rare earth include high cerium rare earth, medium cerium and medium zirconium rare earth, previous metal oxides, previous noble metals and cobalt black material; The secondary rare earth main material includes high-zirconium rare earth, medium-cerium and medium-zirconium rare earth, secondary metal oxides and secondary noble metals; The cerium content of the high cerium rare earth is 50wt%~60wt%; the cerium content of the medium cerium zirconium rare earth is 30wt%~40wt%, and the zirconium content is 40wt%~50wt%; the zirconium content of the high zirconium rare earth is 60wt%~70wt%; The front-stage metal oxide and the rear-stage metal oxide each independently include one or more of nano titanium dioxide, nano aluminum oxide, and lanthanum-modified aluminum oxide; The front-stage active material and the rear-stage active material each independently include an organic acid and a metal salt; The metal salt is one or more of cobalt salt, manganese salt, barium salt and nickel salt; The front-stage auxiliary materials and the rear-stage auxiliary materials independently include a thickener, a pH regulator and water; The front-stage noble metal includes Pt, Pd and Rh; the rear-stage noble metal includes Pd and Rh; The preparation method of the cobalt black material comprises the following steps: Lanthanum nitrate, cerium nitrate, cobalt nitrate, and ferric nitrate are stirred and mixed with deionized water at 80°C until dissolved, aluminum oxide is added and stirred and mixed until a viscous mass is formed, and the viscous mass is dried and roasted to obtain a cobalt black material; wherein the roasting temperature is 750-760°C, and the time is 2.5h; the mass ratio of aluminum oxide, lanthanum nitrate, cerium nitrate, cobalt nitrate and ferric nitrate is 26:4:12:46:12; and the cobalt content of the cobalt black material is 46wt%.
2. The methanol fuel automobile exhaust purification catalyst according to claim 1, characterized in that: The nano titanium dioxide is tungsten-containing nano titanium dioxide, and the tungsten content is 2wt%-10wt%.
3. The methanol fuel automobile exhaust purification catalyst according to claim 1, characterized in that: The organic acid is one or more of citric acid, malic acid, oxalic acid and tartaric acid.
4. The methanol fuel automobile exhaust purification catalyst according to claim 1, characterized in that: The thickener is one or both of aluminum sol and cellulose thickener; the pH regulator is an acidic pH regulator.
5. The methanol fuel automobile exhaust purification catalyst according to any one of claims 1 to 4, characterized in that: In parts by weight: The raw materials of the preceding catalyst include 1500-1520 parts of preceding rare earth main material, 80-111 parts of preceding active material and 3846-4210 parts of preceding auxiliary material; The raw materials of the rear-stage catalyst include 1500 parts of rear-stage rare earth main material, 90 parts of rear-stage active material and 4210-4212 parts of rear-stage auxiliary material; The main material of the previous rare earth includes 580-700 parts of high cerium rare earth, 300-400 parts of medium cerium and medium zirconium rare earth, 500-510 parts of the previous metal oxide, and 5-30 parts of cobalt black material; The secondary rare earth main material comprises 700-800 parts of high-zirconium rare earth, 200-300 parts of medium-cerium and medium-zirconium rare earth, and 500 parts of secondary metal oxide.
Citation Information
Patent Citations
Low-temperature catalytic purification nitrogen oxide catalyst and preparation method thereof
CN112452321A
Doped transition metal oxide and preparation method and application thereof
CN114620772A
Cited By
Low-precious-metal methanol tail gas deep oxidation catalyst and preparation method thereof
CN122582957A